Physical, structural and thermal properties of bio-phenolic/epoxy polymers blends - Ismail, Ahmad Safwan; Jawaid, Mohammad; Hamid, Norul Hisham; Yahaya, Ridwan; Hassan, Azman; Sarmin, Siti Noorbaini (Elsevier, 2023)
Research on polymer has increased to produce a material that has better performance at a lower price. Blending different types of polymer resin in a single system can improve the overall performance of the composite. The effects of bio-phenolic on epoxy’s physical characteristics, FTIR, dynamic mechanical properties, thermal stability, and differential scanning calorimeter were explored in this work. Different loadings of Bio-phenolic were added into epoxy resin, which were 5 wt (P-5), 10 wt (P-10), 15 wt (P-15), 20 wt (P-20) and 25 wt (P25). As a control, pure bio-phenolic (P) and epoxy (E) were fabricated as well. The following tests were performed: density, void content, water absorption, FTIR, Dynamic mechanical analysis (DMA), thermal gravimetry analysis (TGA), and differential scanning calorimeter (DSC). The experimental density of the fabricated polymer is slightly lower compared to the theoretical density. P-25 has the highest experimental density which is 1.12 g/ cm3 . The void content of the polymer blends is less than 5 and the lowest is shown by P-5 which is 2.49. The water absorption is decreased with the addition of bio-phenolic and the water absorption of the polymer is less than 1. The dynamic mechanical analysis reveals that the incorporation of bio-phenolic into epoxy has improved the storage modulus and loss modulus. The glass transition temperature of the polymer blends from DSC is between 61.70 ℃ and 62.32 ℃. While glass transition of polymer blends form loss modulus curve is between 64.97 ℃ and 75.69 ℃. As the bio-phenolic content of polymer blends improved, so did their thermal stability. The FTIR spectra reveal the peak intensity of a few functional groups has decreased with the increasing bio-phenolic content, and this indicates that there is a reaction between the bio-phenolic and epoxy